Adapting Nuclear Security Education Programs in Arab Countries - Ahmed Ahmed M. Alqasimi Alanazi; Mostafa Kofi (International Journal of Nuclear Security, 2023)
Recent times have witnessed considerable international efforts in developing and supporting nuclear security education. However, Arab countries continue to face certain obstacles in the development and implementation of nuclear security education programs. By providing an overview of the nuclear security program at Naif Arab University for Security Science, this study highlights the hurdles faced by Arab countries in implementing new academic programs and improving the quality of current programs in nuclear security. It also discusses the state of the art in nuclear security education and highlights important issues related to such education in the Arab world. However, the influence of nuclear security educational programs in Arab countries was not considered because it requires a separate, detailed analysis.
Keywords: Nuclear Security Education; Safety and Security; Education; Training